Transformation, politics and implementation: smart implementation in governance programs - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos, 2017)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps? Through theoretical considerations and nine case studies, the GIZ traces implementation processes and identifies underlying guiding principles which provide the flexibility and adaptability that is necessary for acting in complex contexts. Main findings show that an adaptive and reflexive management structure is crucial for successful implementation. Quick iteration and tight feedback loops facilitate adaptation and reorientation. Contextsensitive knowledge and constant monitoring create a space for learning and innovation. A joint vision for the future which is used for orientation purposes and can be modified according to new findings and developments fosters fruitful cooperation.

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT